Datalogger prototyping for NH3 ground-level concentrations measurements and comparison with NH3-IASI generated datamaps - Menakh, Imane Nadjah; Benabadji, Noureddine; Menakh, Farid (AIUB Journal of Science and Engineering (AJSE), 2024)
Ammonia (NH3) is a highly dangerous gas due to its toxicity and irritating properties which cause severe eye burns and respiratory problems (throat and lung damages) when inhaled in high concentrations. It is a colorless gas, with a strong suffocating odor. It is also a flammable gas (potentially forming explosive mixtures with air when heated). Ammonia readily dissolves in water to form ammonium hydroxide solution (NH4OH), a highly corrosive agent that can damage metallic structures such as bridges, boats, water tanks, etc… It can also react with other atmospheric pollutants, primarily SO2 and NOx, generating fine particulate matter which can pass through the lungs into the bloodstream, posing great health risks. On the other hand, it is also considered as an industrial useful hydrogen carrier of energy, and an additive for coal-fired power plants, and is slowly repurposed from its natural role as a fertilizer in the agricultural industry to a “green and clean” fuel source. In this article, we describe in detail the use of an electrochemical sensor driven by a microcontroller. The principle of the measurement system is a chemical oxidation of catalyst metals, where conductivity varies with the target gas concentration. Mathematical calculations are also provided to convert the 10-bit numerical counts to meaningful NH3 concentrations in ppm, taking into account the temperature dependency correction. As a final stage, 4 months of data acquisition has been carried out in the petrochemical industrial city of Arzew.